A Descriptive study on the working conditions and perceived quality of life of selected home-based and community-based women weavers in Benguet Province - Estrella, Kathleen Ninette I. (College of Home Economics, University of the Philippines Diliman, 2020)
Among the six million home-based workers in the Philippines, many are women weavers from Benguet. These weavers play a vital role in the progress of Benguet Province's weaving and tourism industry. However, they continue to be among the city's poorest and experience atypical working conditions. Given the significant roles that they play, it is just right to ensure that they are able to uplift their quality of life. The study aimed to describe the working conditions and perceived quality of life of selected home-based women weavers in Benguet Province. Through the course of the research, another type of work set-up was found. These are the community-based women weavers. The study covered three different communities in Benguet. The respondents were chosen through non-probability convenience sampling. There were a total of nine respondents. The data was gathered through individual and group interviews. Findings show that both the home-based and community-based women weavers' existing work conditions are substandard as compared to existing standards provided in different labor laws and legislations. Despite this, the weavers are satisfied with their perceived quality of life because they give more importance to being able to economically provide for their families than the working conditions they experience. Furthermore, the individual weaver's experience of wellness is rooted in their family's collective condition. If the family is able to meet their physical and economic needs, the individual weaver's wellness and over-all quality of life are also satisfied. There were many home-based weavers from different communities that the researcher was able to cover. The study could be improved by covering more weaving and craft communities done by home-based weavers and community-based weavers. Methodological improvements as well as future studies, such as the weaver's situation in relation to their productivity are recommended in the study.